2017
DOI: 10.1093/scan/nsw170
|View full text |Cite
|
Sign up to set email alerts
|

Trust as commodity: social value orientation affects the neural substrates of learning to cooperate

Abstract: Individuals differ in their motives and strategies to cooperate in social dilemmas. These differences are reflected by an individual’s social value orientation: proselfs are strategic and motivated to maximize self-interest, while prosocials are more trusting and value fairness. We hypothesize that when deciding whether or not to cooperate with a random member of a defined group, proselfs, more than prosocials, adapt their decisions based on past experiences: they ‘learn’ instrumentally to form a base-line exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…In a multi-round trust game with the same partner and roleswitching, men may have been more motivated to always trust as trustors to signal their trustworthiness to maximize profits. Greater PreC responses are consistent with males' enhanced tendency to use self-referencing to infer the strategies of partners in the repeated trust game (Lambert et al, 2017). This confirms a prior study suggesting that PreC activations are linked to attempts to understand the responsiveness of others (Sakaiya et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…In a multi-round trust game with the same partner and roleswitching, men may have been more motivated to always trust as trustors to signal their trustworthiness to maximize profits. Greater PreC responses are consistent with males' enhanced tendency to use self-referencing to infer the strategies of partners in the repeated trust game (Lambert et al, 2017). This confirms a prior study suggesting that PreC activations are linked to attempts to understand the responsiveness of others (Sakaiya et al, 2013).…”
Section: Discussionsupporting
confidence: 84%
“…Social decision-making involves interdependency and mutual commitment; individuals must consider not only how possible outcomes will affect them, but also how those outcomes will affect other people with similar or conflicting needs and desires [ 1 ]. Functional magnetic resonance imaging (fMRI) studies that have modelled social interaction using the Prisoner’s Dilemma (PD) paradigm have typically targeted neural activity during isolated snapshots of the process of either making a decision or receiving feedback about one’s decision [ 2 6 ]. The unfolding of the interaction from decision-making, to the anticipation of outcome, to receiving feedback on one’s decision constitutes a “cascade” of events that may be better understood as a dynamic, cyclical flow of interdependent social phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…Four of these studies investigated the neural basis of social cooperation with human co-players [ 2 , 3 , 11 , 12 ]. Findings from the earliest of these studies indicated that decision-making in the iPD game was associated with activity in the rostral anterior cingulate (rACC) and the caudate [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The “homo economicus” model is slowly changing as we begin to accept and accommodate the reality that various factors including emotions (Goel and Dolan, 2003; Goel and Vartanian, 2011; Halperin et al, 2013; Smith et al, 2014, 2015; Goel et al, 2017; Levine et al, 2017; Eimontaite et al, 2018), reward processing (Sanfey et al, 2003), Theory of Mind (Camerer, 2003) and individual differences in cognitive inhibition (De Neys et al, 2011), social orientation (Emonds et al, 2014), and trust (Chaudhuri et al, 2002; Lambert et al, 2017) modulate our decision-making. In fact, trust and cooperation are hard to separate and quite often these terms are used interchangeably while investigating social interaction games (Yamagishi et al, 2005).…”
Section: Introductionmentioning
confidence: 99%